ACADEMIC CULTURE INSYEKH ABDUL HALIM HASAN BINJAI INSTITUTE - Asry, Wina; Nasution, Wahyudin Nur; Arsyad, Junaidi (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This research aims to analyze (1) the Implementation of Lecturer and Student Academic Ethics at the Syekh Abdul Halim Hasan Binjai Institute, (2) the Implementation of Lecturer and Student Academic Activities at the Syekh Abdul Halim Hasan Binjai Institute, (3) the Implementation of Lecturer and Student Academic Work at the Sheikh Institute Abdul Halim Hasan Binjai. This type of research is qualitative research with a phenomenological approach: the research data collection instrument used observation, interviews, and documentation techniques. The results of the discussion of research data obtained the following conclusions: (1) Implementing academic ethics for lecturers and students on the Syekh Abdul Halim Hasan Binjai Institute campus applies various forms of sound and correct academic attitudes and behavior values. (2) Implementation of academic activities for lecturers and students on the Syekh Abdul Halim Hasan Binjai Institute campus has implemented all activities while in the campus academic environment, starting from learning activities, research, service, and other activities that support the tri dharma of higher education. (3) Implementing the academic work of lecturers and students on the Syekh Abdul Halim Hasan Binjai Institute campus has produced scientific essays based on facts and written according to the applicable writing methodology.